2008
DOI: 10.3332/ecancer.2008.83
|View full text |Cite
|
Sign up to set email alerts
|

Syzygium Cumini Inhibits Growth and Induces Apoptosis in Cervical Cancer Cell Lines: A Primary Study

Abstract: Cervical cancer is common among women in the Indian subcontinent and the incidences and death rates are gradually increasing over the years. Several dietary phytochemicals have been reported to have growth inhibitory and apoptotic effect on HeLa and other cervical cell lines. In this study, using Hoechst 33342 staining, MTT, Annexin V-FLUOS/PI and TUNEL assays we demonstrated that Syzygium cumini extract inhibits the growth and induces apoptosis in HeLa and SiHa cervical cancer cell lines in a dose- and time-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 49 publications
2
20
0
1
Order By: Relevance
“…Similarly, the effect of 50% methanol extract showed greater apoptosis in HeLa than SiHa cells. 110 Freeze-dried Jamun fruit pulp extract was found to inhibit cell proliferation and growth of MCF-7 cells and MDA-MB-231 breast cancer cells in a concentration-and time-dependent manner; however, it was less effective in the MCF-10A cells. Yet, the Jamun extract did not induce apoptosis in untransformed MCF-10A breast cancer cells, whereas it was quite effective in triggering apoptotic cell death in both MCF-7 cells and MDA-MB-231 breast cancer cells.…”
Section: Anticancer Activitymentioning
confidence: 99%
“…Similarly, the effect of 50% methanol extract showed greater apoptosis in HeLa than SiHa cells. 110 Freeze-dried Jamun fruit pulp extract was found to inhibit cell proliferation and growth of MCF-7 cells and MDA-MB-231 breast cancer cells in a concentration-and time-dependent manner; however, it was less effective in the MCF-10A cells. Yet, the Jamun extract did not induce apoptosis in untransformed MCF-10A breast cancer cells, whereas it was quite effective in triggering apoptotic cell death in both MCF-7 cells and MDA-MB-231 breast cancer cells.…”
Section: Anticancer Activitymentioning
confidence: 99%
“…Studies in the past one decade have also shown that Jamun possess antineoplastic [50]. Radioprotective [51][52][53][54] and chemopreventive effects [55] all of which are useful in the prevention and treatment of cancer.…”
Section: Medicinal Propertiesmentioning
confidence: 99%
“…The best effect was observed at 80 mg/kg but only when administered through the intraperitoneal route as 50% of the animals survived when compare to 22% in the oral route and none in the radiation alone cohorts. The intraperitoneal administration of the organic extract (dichloromethane-methane) of leaves (5,10,20,30,40,50,60 and 80 mg/kg b. wt.)…”
Section: Radioprotective Effectsmentioning
confidence: 99%
“…Pharmacological studies show that S. cumini species have several functions, among them, antioxidants, antibacterial, antifungal, anti-allergic, anti-inflammatory, anti-hyperlipidemic, gastroprotective, cardioprotective, hepatoprotective, anticancer, radioprotective and antidiarrhoeal (Jagetia and Baliga, 2002;Barh and Viswanathan, 2008;Chaturvedi et al, 2009;Schoenfelder et al, 2010;Patel et al, 2010).…”
Section: Introductionmentioning
confidence: 99%